Psychological Problems Of Social Adjustment In Grade 2 Children At Sd N 37 Pagambiran - Wahyuli, Wilma Sil; Azyel, Evelyn Etenia; Ikhsan, Muhammad (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This research is motivated by the difficulty of social adjustment for students. This social adjustment shows that some students find it difficult to understand the lesson, so in this study it can be formulated how teachers and students interact in the classroom. The purpose of this study was to implement the influence of teacher motivation, students' self-confidence in social adjustment in the classroom. This study uses a qualitative method. Data was collected using questionnaires and interviews. Respondents in this study amounted to 4 people. While the qualitative analysis is taken from the interpretation of the data by providing information and explanations. The results showed that student motivation, teacher motivation, and student attitudes with classmates in social adjustment in the classroom. The motivation of other students also has a higher effect on the social adjustment of students with problems